Pojęcie choroby psychicznej w fenomenologicznej perspektywie - Kapusta, Andrzej (Wydawnictwo Naukowe UAM, 2013)
The article presents ongoing discussions on the concept of mental illness, especially its phenomenological approach. The point of departure is Karl Jaspers’ Allgemeine Psychopatologie - important inspiration for the critics of the contemporary psychiatric classifications and biomedical explanations (biological, psychological) that, in general, ignores essential dimensions of morbid experience and don’t regard illness as an action failure of “ordinary doing”. Present-day dispute over the nature of mental illness with such names as Szasz, Boorse, Fulfors reveals a diversity of mental symptoms and its normative character. In spite of the possibilities of multilevel analysis of human’s psychopathology we consider patient’s feelings and experience. Svenaeus’ understanding of mental disorder is presented to demonstrate existential and experiential dimensions of disorder. The analysis of embodied (inspired by Merleau-Ponty’s research) aspects of disorders attempt to overcome the limits between mental and somatic elements of psychiatric disorder.

Artykuł przedstawia bieżącą dyskusję na temat pojęcia choroby psychicznej, szczególnie zaś jego fenomenologicznych ujęć. Punktem wyjścia analiz są refleksje Karla Jaspersa poświęcone zjawisku choroby. Poglądy autora Allgemeine Psychopathologie stanowią ważną inspirację dla wielu badaczy krytykujących współczesne klasyfikacje psychiatryczne oraz biomedyczne wyjaśnienia (biologiczne, psychologiczne), które na ogół ignorują istotny wymiar chorobowego doświadczenia oraz nie traktują choroby jako niepowodzenia w codziennej ludzkiej aktywności. Nawiązanie do współczesnego sporu o naturę choroby psychicznej z teoriami Szasza, Boorse’a, Kendella, Fulforda pokazuje różnorodność i normatywny charakter tego pojęcia. Pomimo możliwości podjęcia różnych poziomów opisu patologii ludzkiego umysłu podkreśla się konieczność uchwycenia zaburzeń psychicznych poprzez uwzględnienie doznań i doświadczeń pacjenta. Koncepcja choroby Svenaeusa pokazuje egzystencjalny i doświadczeniowy wymiar choroby, natomiast analizy cielesnego wymiaru choroby ukazują, w duchu Merleau-Ponty’ego, brak możliwości postawienia ostrej granicy między ciałem i umysłem, a w konsekwencji – cielesny wymiar zaburzeń psychicznych.
The Concept of Mental Illness in Phenomenological Perspective
Keywords: mental illness; Karl Jaspers; phenomenology; embodiment